Increase of atypical fibroxanthoma and pleomorphic dermal sarcoma: a retrospective analysis of four German skin cancer centers. (28th November 2022) - Kuntz, Thomas; Siebdrath, Julian; Hofmann, Silke C.; Baltaci, Mehmet; Schaller, Jörg; Hellmich, Martin; von Goltzheim, Luise Stach; Assaf, Chalid; Oellig, Frank; Michalowitz, Alena‐Lioba; Helbig, Doris; Kreuter, Alexander
Summary: Background and objectives: In recent years, considerable insight has been gained into the pathogenesis, diagnosis and treatment of cutaneous sarcomas, including atypical fibroxanthoma (AFX) and pleomorphic dermal sarcoma (PDS). Both entities have shown increasing incidence rates in the last decade. This study was initiated to evaluate how these new insights impact the number of diagnoses of AFX/PDS compared to other cutaneous sarcoma entities. Patients and methods: In a retrospective study of four German skin cancer centers, all histopathological reports of cutaneous sarcomas (AFX, PDS, dermatofibrosarcoma protuberans, cutaneous leiomyosarcoma, angiosarcoma, and Kaposi sarcoma) confirmed by board‐certified dermatopathologists were analyzed during a time‐period of seven years (2013–2019). Additionally, utilization of immunohistochemical markers (including pan‐cytokeratin, S100, desmin, CD34, CD10, procollagen‐1, CD99, CD14, and CD68) as an adjunct to diagnose AFX/PDS was recorded. Results: Overall, 255 cutaneous sarcomas were included in the present study. The diagnosis of a cutaneous sarcoma has consequently risen from 2013 to 2019 (from 16 to 52 annual cases). The results of AFX/PDS revealed 4.6 times more diagnoses in 2019 than in 2013. Atypical fibroxanthoma represented the most common subtype, displaying 49.3 % of all diagnosed cutaneous sarcomas. Additionally, the increase of AFX/PDS was linked to the use of immunohistochemistry, with specific immunohistochemical markers used in 57.1 % of cases in 2013 compared to 100 % in 2019. Conclusions: This retrospective study of four German skin cancer centers demonstrates a substantial rise of AFX/PDS, possibly due to recently established diagnostic and terminology standards. This rise is probably linked to increased utilization of specific immunohistochemical markers. Atypical fibroxanthoma/PDS may be more common than previously thought and seems to represent the most frequent cutaneous sarcoma subtype.